2014
DOI: 10.1186/s12955-014-0138-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity does not account for differences in the health-related quality of life of Turkish, Moroccan, and Moluccan elderly in the Netherlands

Abstract: BackgroundData on how different groups of elderly immigrants perceive health-related quality of life (HRQOL) is scarce and research on the influence of ethnicity on HRQOL across ethnic groups is missing. Measuring HRQOL may help to detect cross-cultural differences and to decide whether ethnic-specific health and prevention programmes are required to improve HRQOL. We investigated differences in HRQOL among three elderly immigrant populations with a special focus on the contribution of ethnicity, in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
0
20
1
Order By: Relevance
“…In addition, ethnicity was an important predictor of mental health care use in young children [73]. With regards to the effect of ethnicity on mental health, the current results were not in line with the findings from other studies which ethnicity could not efficiently predict adult mental health [74] and accounted for differences in the health-related quality of life of international migrants [75]. The findings were consistent with the view that ethnicity itself was not related to disparities in mental health [76].…”
Section: Discussioncontrasting
confidence: 88%
“…In addition, ethnicity was an important predictor of mental health care use in young children [73]. With regards to the effect of ethnicity on mental health, the current results were not in line with the findings from other studies which ethnicity could not efficiently predict adult mental health [74] and accounted for differences in the health-related quality of life of international migrants [75]. The findings were consistent with the view that ethnicity itself was not related to disparities in mental health [76].…”
Section: Discussioncontrasting
confidence: 88%
“…The overall response rate of 24 % was disappointingly low [ 36 ]. This response rate is lower than the reported response rates achieved in studies among other minority groups in the Netherlands and which are generally above 40 % [ 37 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used the total score for each subscale, which ranges from 5 to 25 with higher scores indicating greater loneliness. Loneliness is a well-known determinant of quality of life [ 28 – 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Convergent validity of the WHOQOL-OLD was also determined by examining the correlations between on the one hand the six WHOQOL-OLD facets and on the other hand quality of life measured by four WHOQOL-BREF domains (physical health, psychological, social relations, environmental), the SF-12 physical component summary and mental component summary, the three TFI domains, and the two subscales of the ESLS (emotional loneliness, social loneliness). The TFI and ESLS were included because previous research has shown that quality of life is closely associated with frailty [ 18 , 27 , 39 ] and loneliness [ 28 – 30 ]. Sufficiently high correlations (operationalized as larger than .3) between similar scales support convergent validity.…”
Section: Methodsmentioning
confidence: 99%